Insects As an Alternative Protein Source (Texas Journal of Multidisciplinary Studies, 2021)
This article analyzes the synthesis of the Tenebrio molitor protein (Coleoptera: Tenebrionidae) belonging to a food insect, depending on its nutrient content. Differences in protein synthesis by Tenebrio molitor larvae were shown when wheat bran and flour from the macrophytes Lemna minor and Azolla carolina were added. In particular, it was noted that TMO-2 and TMO-6 T.molitor F6 larvae are synthesized on average 31.02% protein in wheat bran, 38.13% in duckweed and 30.87% in azole.